Genomic surveillance of emerging SARS-CoV-2 Omicron variations in Tianjin Municipality, China 2022 - Xin Gao; Ming Zou; Yue Lei; Zhaolin Tan; Zhichao Zhuang; Baolu Zheng; Aiping Yu; Yanzhen Han; Xiaohui Lu; Xiaochang Liu; Ying Wang; Yuan Wang; et al. (Elsevier, 2024)
The coronavirus disease 2019 (COVID-19) pandemic caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has severely impacted public health. In 2022, the Omicron variant of SARS-CoV-2 rapidly became the dominant circulating variant in the local COVID-19 outbreaks in Tianjin Municipality, China. To gain a deeper understanding of the genetic variations of the Omicron variant in Tianjin, specimens from individuals who tested positive for SARS-CoV-2 between December 2021 and November 2022 were used for virus whole genome sequencing and phylogenetic analysis. A total of 1,674 high-quality Omicron sequences were obtained, consisting of 1,339 sequences from local cases belonging to 20 Phylogenetic Assignment of Named Global Outbreak (PANGO) lineages and 335 sequences from imported cases belonging to 70 lineages. Tianjin experienced five waves of local outbreaks, accompanied by multiple substitutions among subvariants, ranging from the initial BA.1.1 lineage to the subsequent BA.2, BF.7, and BA.5.2 lineages. The evolutionary rate of local strains, estimated to be 28.999 substitutions per year, and the evolutionary rate of imported strains, estimated to be 24.946 substitutions per year, were lower than that of the strains circulating globally. The additional substitutions and deletions of local strains have been used to identify and disrupt the virus transmission chains. The subvariants such as BA.5.2.48, BA.5.2.49, BF.7.14, and XBB.1 circulating in the fifth epidemic wave presented criterial immune escape mutations including S: R346T, S: L452R and S: F486V. It is essential to implement genomic surveillance strategies to investigate further the development of genomic mutation characteristics in the SARS-CoV-2 variant. This ongoing monitoring will contribute to a better understanding of the virus's genetic changes and aid in effective control measures.